Kampanye Konservasi Sungai Di Kuningan Melalui Animasi Pendek - Yulyanto; Rika Nugraha; Abi M Rasul (Bulletin of Information Technology (BIT), 2022)
The increase in population has also resulted in changes in the pattern of people's consumption of water sources, but today there are still many people who are still not aware of maintaining their water sources including rivers, in Kuningan, especially in the Kuningan village area, there are rivers that used to be clean slowly become dirty due to garbage and waste, the purpose of this research is so that the community, especially children, know more about the importance of protecting the environment, especially the rivers around it. The results of this study made a short animated film entitled Tirta & Yahsa "the river is not a trash can" which contains the importance of conserving or preserving rivers, as a media for campaigns and education for the community, especially children to raise awareness about the importance of conserving or preserving rivers. After it was published offline to elementary school children and online on the YouTube channel, it got a very positive response from children and the public in general liked the animation, even from the 26 children who were tested watching it offline 100% all of them liked this animation. and 77% or 20 children were directly affected by starting from small things around them such as cleaning their respective desks and not littering, while 23% or 6 children did not get a direct impact because their desks still looked unclean